The Studio in the Seminar: Performing Theory in an MFA Classroom - Shankar, Karin; Steinmetz, Julia (Performance Matters)

(untitled) (Institute for Performance Studies, Simon Fraser University, 2023)
This article describes an "Introduction to Performance Theory" course that the authors co-teach to MFA students at Pratt Institute in Brooklyn, New York. Through the semester, we track genealogies of performance studies, highlighting the ways in which our interdiscipline has been incorporated as an academic field while still remaining sensationally unsettled in its interventions, methods, and objects of analysis. The focus of this article is on the ways we have tailored a performance theory course to serve MFA students—artists and makers across genre and discipline. The article offers our syllabus and ten practice-based assignments to illustrate how we encourage the artists in our class to engage with critical theory and performance studies scholarship in an embodied way. Bringing the studio into the seminar, our MFA students stage performance experiments related to each week’s readings. Our syllabus is accompanied by a reflection on co-teaching performance studies as a dynamic couple form that itself constitutes a performance of pedagogy, an enactment of sociality, and an embodiment of theory.